Analisis Risiko Kadar Enzim SGOT dan SGPT pada Penderita Diabetes Mellitus Tipe 2 - Mochamad Rizal Maulana; Sutji Kuswarini (Jaringan Laboratorium Medis, 2022)
Diabetes mellitus is a group of metabolic diseases that occur due to abnormalities in insulin secretion and/or insulin action. In type 2 diabetes mellitus there is a decrease in glucose absorption by the body due to insulin resistance. Energy metabolism from glucose is processed through the synthesis of fatty acids in the liver (cytosol). The process that occurs continuously causes the accumulation of lipids in the liver or "fatty liver" so it is necessary to check the levels of transaminase enzymes which include SGOT and SGPT. The purpose of this study was to analyze the levels of SGOT and SGPT enzymes in patients with type 2 diabetes mellitus using the analytical observational method. The results of the examination of SGOT and SGPT levels from 30 patients who were taken randomly at Dr. Soetomo Surabaya will be analyzed with bar graphs and diagrams. Of 30 random samples, 20 samples (66.67%) had SGOT levels above the normal value, and 12 samples (40%) had SGPT with results above normal values. This study concludes that there is an increase in the levels of SGOT and SGPT enzymes in patients with type 2 diabetes mellitus.